2019
DOI: 10.3390/jcm8050641
|View full text |Cite
|
Sign up to set email alerts
|

Cranio-Facial Characteristics in Children with Autism Spectrum Disorders (ASD)

Abstract: Background: Cranio-facial anomalies frequently occur in neurodevelopmental disorders because both face and brain are derived from neuroectoderm. The identification of differences in the facial phenotype of children with Autism Spectrum Disorders (ASD) may reflect alterations in embryologic brain development in children with ASD. Methods: we evaluated 33 caucasian children with ASD using a 2D computerized photogrammetry. Anthropometric euclidean measurements and landmarks located on the soft tissue of the face … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(49 citation statements)
references
References 25 publications
1
45
0
Order By: Relevance
“…The correlations between anthropometric z-scores, demographic characteristics, global QI, CARS and MND are shown in Table 3. Most of these correlations were previously described in our study [11]. Moreover, significant, large positive correlations were found between cephalic index and sensory deficits (r = 0.547, p-value < 0.001) and between cephalic index and c-MND (r = 0.469, p-value = 0.005).…”
Section: Resultssupporting
confidence: 84%
See 4 more Smart Citations
“…The correlations between anthropometric z-scores, demographic characteristics, global QI, CARS and MND are shown in Table 3. Most of these correlations were previously described in our study [11]. Moreover, significant, large positive correlations were found between cephalic index and sensory deficits (r = 0.547, p-value < 0.001) and between cephalic index and c-MND (r = 0.469, p-value = 0.005).…”
Section: Resultssupporting
confidence: 84%
“…Our recent research [11] identified a dolichocephalic head shape in ASD children, which did not correlate with autism severity. This finding was compatible with previous research, showing that brain and head size is a relatively non specific finding in autism [27] and suggesting an abnormal brain growth trajectory during the in-utero period, after the 22nd week of amenorrhea, in children with ASD who showed postnatal head overgrowth [31].…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations